IMPACT OF SYARIAH COMPLIANCE PERCEPTION AND INVESTMENT KNOWLEDGE ON SYARIAH STOCK INTEREST AMONG STUDENTS - Alwi, Irfriyandika; Nuh, Ahmad; Eddy Wibowo, Finantyo (Jurnal Impresi Indonesia, 2023)
The advancement of technology and innovation in the capital market has significantly impacted public interest and participation in investment. This study aims to analyze the influence of factors such as perception of Syariah compliance and investment knowledge, as well as the combined impact of these factors on students' interest in investing in Syariah-compliant stocks in the Syariah capital market. The research employs a quantitative approach to the population of undergraduate students majoring in Islamic Economics and Sharia Economics Law at STIS AL-WAFA. The sample consists of 147 students selected through a questionnaire method. Validity, reliability, classical assumption tests, and multiple linear regression analysis are used for data analysis. The study's findings reveal that perception of Syariah compliance is insignificant in students' interest in investing in Syariah-compliant stocks at STIS AL-WAFA. Knowledge about Syariah investment significantly impacts students' interest in investing in Syariah-compliant stocks in the Syariah capital market. Perception of Syariah compliance and knowledge about Syariah investment jointly influence students' interest in investing in Syariah-compliant stocks in the capital market. Nevertheless, it is acknowledged that other factors not covered in this study might also influence students' interest in investing in Syariah-compliant stocks in the capital market. Therefore, in this context, understanding and reinforcing these factors are crucial to stimulate students' interest in investing in Syariah-compliant stocks in the Syariah capital market.